Alcohol septal ablation in patients with hypertrophic obstructive cardiomyopathy: low incidence of sudden cardiac death and reduced risk profile. Issue 14 (3rd May 2013) - Jensen, Morten K; Prinz, Christian; Horstkotte, Dieter; van Buuren, Frank; Bitter, Thomas; Faber, Lothar; Bundgaard, Henning
Abstract : Background: The infarction induced by alcohol septal ablation (ASA) may predispose to arrhythmia and sudden cardiac death (SCD). Objective: To assess survival, incidence of SCD after ASA and effects of ASA on the traditional risk factors (RFs) for SCD. Design: An observational cohort-study (follow-up 8.4±4 years). Setting: A dual-centre cohort. Patients: 470 consecutive patients (age 56±14 years) with obstructive hypertrophic cardiomyopathy (HCM) (1996–2010). Interventions: Clinically applied echo-contrast-guided ASA treatments. Main outcome measures: All-cause mortality, SCD and RFs for SCD before and after ASA. Results: The 10-year survival was 88% (annual all-cause death rate 1.2%) after ASA compared with 84% (p=0.06) in a matched background population. The 10-year survival free of SCD was 95% (annual SCD rate 0.5%). ASA reduced the prevalence of abnormal blood pressure response (from 23% to 9%, p<0.001), syncope (26% to 2%, p<0.001), non-sustained ventricular tachycardia (NSVT) (23% to 17%, p<0.05) and maximal wall thickness ≥30 mm (7% to 2%, p<0.001). There was a family history of SCD in 19% of the patients. The proportion of patients at high risk—that is, two or more RFs (n=89), was reduced from 25% to 8% (p<0.001). A RF score ≥2 before ASA was not associated with SCD (n=361, p=0.31). Conclusions: Survival in ASA-treated patients was similar to that in the background population. The number of RFs, including the prevalence of NSVT, was markedly reduced by ASA and the incidence of SCD was correspondingly low. Thus, clinically applied ASA was safe.